Influence of homogenization treatment on the degradation behavior of Zn-3Mg alloy in simulated body fluid solution - Dambatta, M.; Kurniawan, Denni; Sudin, I.; Yahaya, B.; Hermawan, H. (Sage, 2016)
This paper reports a degradation study of Zn-(3 wt%) Mg alloy proposed for biodegradable medical implants. The alloy was cast from high-purity raw materials and homogenized at 370 ° C for 15 h under vacuum and water quenched. The effect of homogenization on microstructure and degradation behavior in simulated body fluid was investigated. Results showed that homogenization transformed the star-like dendritic Zn-rich shape into a network of precipitate phase along eutectic colony and dispersed M g2 zn 11 phase. The homogenized alloy showed higher degradation resistance compared to the as-cast alloy, pure Zn, and pure Mg samples. The relationship between microstructure and degradation behavior discussed further in this paper.